Improving performance: what pastoral counselors can do? - Pedhu, Yoseph (Indonesian Institute for Counseling, Education, and Therapy & Indonesian Counselor Association, 2020)
Pastoral counselor performance is considered to impact on client wellbeing. The performance of pastoral counselors refers to their performance in doing counseling. This article explores the performance of pastoral counselors and strategies to improve it. The author examines the concepts and factors that contribute to the performance of counselors. Previous research on performance is reviewed. Based on this review, the author elaborates on some strategies that can help pastoral counselors improve their performance in carrying out pastoral counseling.